Entangled: A New Archaeology of the Relationships between Humans and Things - Hodder, Ian 1948- (New Jersey Blackwell, 2024)
"This is a substantial revision of the first edition. Perhaps most importantly I have now included a chapter on human to human entanglements and have pulled human relations more into the center of entanglements. This results from my critique of the notion of symmetry between humans and things that has widely been touted in recent years in archaeology and related disciplines but has raised ethical issues with which I concur and discuss in this volume. Another important change is that I have, after further thought, retreated from the notion of 'things-in-themselves' and from the object nature of things. I was wrong in the first edition to argue that things can exist outside their relations. The result is a more fully relational stance. I have also paid greater attention to flows and temporality. The greater focus on relationality is underpinned by a recognition that all things and humans are in flux. Change through time undermines notions of the fixed spatial extension of things. There is thus greater attention paid to the forces that generate flows, and an overall shift from being to becoming."
First edition in 2012
Keywords: Archeology; Material culture; Phenomenology